1975
DOI: 10.1007/bf00332380
|View full text |Cite
|
Sign up to set email alerts
|

Two new genes controlling the constitutive acid phosphatase synthesis in Saccharomyces cerevisiae

Abstract: Two new classes of mutants, phoF and phoG, lacking the constitutive acid phosphatase activity, were isolated. They both complemented each other and the phoC mutation. No linkage was detected among these three complementary genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Transformants of the f/ti2(,dod) mutant, K272-7c, harboring the low-copy numbered vector plasmid YCp50, pRS316 and four plasmid (pTSR1, pTSR2, pTSR3 and pTSR4) were cultured in the absence of thiamin and assayed for T-rAPase activity ( Table I). The T-rAPasc activity in these transformants harboring the T1//2(PH06) gene was less active than the wild-type strain and its activity in the recipient cells transformed with the control plasmid, YCp50 and pRS3 16, were as markedly low as that of the dti2(phu6) mutant, OS&MS [2]. Furthermore, the activity in these transformants with pTSR1, pTSR2 and pTSR3 was repressed by thiamin (_ 3 x lo-' M) in the minimal medium in the same manner as that of the wild-type strain.…”
Section: Expwssion Of Ffte Uctivifies Of T-rapuse Und Cii-mentioning
confidence: 87%
See 2 more Smart Citations
“…Transformants of the f/ti2(,dod) mutant, K272-7c, harboring the low-copy numbered vector plasmid YCp50, pRS316 and four plasmid (pTSR1, pTSR2, pTSR3 and pTSR4) were cultured in the absence of thiamin and assayed for T-rAPase activity ( Table I). The T-rAPasc activity in these transformants harboring the T1//2(PH06) gene was less active than the wild-type strain and its activity in the recipient cells transformed with the control plasmid, YCp50 and pRS3 16, were as markedly low as that of the dti2(phu6) mutant, OS&MS [2]. Furthermore, the activity in these transformants with pTSR1, pTSR2 and pTSR3 was repressed by thiamin (_ 3 x lo-' M) in the minimal medium in the same manner as that of the wild-type strain.…”
Section: Expwssion Of Ffte Uctivifies Of T-rapuse Und Cii-mentioning
confidence: 87%
“…and after centrifugation at 28.000 x g for 30 min 111~ supernatant was used as a crude extract. Overall thiamin-synthesizing enzyme activity from hydroxymcthylpyrimidine and hydroxycthylthiazolc and the activity of thiamin phosphate pyrophosphorylasc were assayed as previously described [3] The thi2(pho6) mutant defective in a regulatory gene for the synthesis of T-rAPase [2] was auxotrophic for thiamin, and the activities of enzymes involved in thiamin synthesis were markedly low in the crude extract from the thi2(pho6) mutant [3]. However, as shown in Fig.…”
Section: Sfraim Mtd Rrrdiumentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, apho6 mutant defective in the regulatory gene for the synthesis of periplasmic T-rAPase encoded by the PHO3 gene (26,27) is auxotrophic for thiamine, and the enzyme activities involved in thiamine synthesis described above are markedly low in crude extracts of this mutant (9). This indicated that the expression of structural genes for T-rAPase and the enzymes involved in thiamine biosynthesis was regulated positively by PHO6.…”
mentioning
confidence: 99%
“…PHO2 mutants lack only the repressible APase (26,28). PHO6 and PHO7 affect expression of PHO3, the "constitutive" APase (23), and PHO9 encodes a protease involved in AlkPase maturation (9).…”
mentioning
confidence: 99%